The Cambridge Introduction to Edward Said / [electronic resource] - McCarthy, Conor (Cambridge : Cambridge University Press, 2010)
One of the most famous literary critics of the twentieth century, Edward Said's work has been hugely influential far beyond academia. As a prominent advocate for the Palestinian cause and a noted music critic, Said redefined the role of the public intellectual. In his books, as scholarly as they are readable, he challenged conventional critical demarcations between disciplines. His major opus, Orientalism, is a key text in postcolonial studies that continues to influence as well as challenge scholars in the field. Conor McCarthy introduces the reader to Said's major works and examines how his work and life were intertwined. He explains recurring themes in Said's writings on literature and empire, on intellectuals and literary theory, on music and on the Israel/Palestine conflict. This concise, informative and clearly written introduction for students beginning to study Said is ideally set up to explain the complexities of his work to new audiences.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Said, Edward W